The Role of the Balanced Scorecard’s Learning and Growth Perspective in Enhancing Employee Performance: A Narrative Review - Ayodeji, Ilesanmi Oladele; Ojo, Emmanuel Olusola; Aladelusi, Kehinde; Badiru, Nafiu (NIU Journal of Management Sciences; Vol 12 No 2 (2026): NIU Journal of Management Sciences, Vol. 12, No. 2, June 2026DO - 10.58709/niujms.v12i2.2505, 2026)
Balanced Scorecard (BSC) has emerged as one of the most popular strategic management approaches used to connect the organization's objectives and strategies to performance measurement. The learning and growth perspective is one of four perspectives that emphasize the development of employee skills, organizational learning, information systems, and enabling workplace culture for improving performance. This narrative review aims to provide a synthesis of findings from studies published between 2021 and 2026, to examine the role of the learning and growth perspective in contributing to employee performance. Peer-reviewed articles published in Scopus, Web of Science and the Directory of Open Access Journals (DOAJ) were employed to source relevant literature. Review concluded that employee training, knowledge sharing, skill development, and organizational learning helps to enhance productivity, innovation, service delivery quality, and overall organizational performance. Healthcare, banking, education, manufacturing, and public sector organizations all demonstrate positive employee and organizational results in relation to learning and growth. The review revealed impediments in measuring intangible assets, resource constraints, empowering employees, and linking learning and growth to the other dimensions of the Balanced Scorecard. The results indicate that companies that focus on developing their workforce, knowledge management programs, and culture of learning are more likely to successfully achieve continuous improvement in their performance. Overall, the study demonstrates the continued importance of the learning and growth perspective in driving employee performance and organizational success. Keywords: Balanced Scorecard, Learning and Growth Perspective, Employee Performance, Organizational Learning, Human Capital, Knowledge Management, Strategic Alignment, Employee Development, Organizational Performance, Performance Management.